The Effect of Price and Product Quality on Purchase Decisions for Imported Used Clothing - sarihayati (Jurnal Ragam Pengabdian, 2026)
This study aims to determine the effect of price and product quality on purchasing decisions on imported used clothing in Sampit City. This study used purposive sampling technique. Respondents of this study amounted to 120 people. The analysis technique used in this research is multiple linear regression analysis using SPSS software version 22. The test results for the Price variable (X1) are equal to 0.008 <0.05. So it can be concluded that Ho is rejected and Ha1 is accepted, meaning that the price variable has a positive and significant effect on purchasing decisions (Y). The test results for the Product Quality variable (X2) are equal to 0.000 <0.05. So it can be concluded that Ho is rejected and Ha2 is accepted, meaning that the product quality variable has a positive and significant effect on purchasing decisions (Y).